2017
DOI: 10.1002/2017ja024027
|View full text |Cite
|
Sign up to set email alerts
|

Spectral properties and associated plasma energization by magnetosonic waves in the Earth's magnetosphere: Particle‐in‐cell simulations

Abstract: In this paper, we perform a 1‐D particle‐in‐cell (PIC) simulation model consisting of three species, cold electrons, cold ions, and energetic ion ring, to investigate spectral structures of magnetosonic waves excited by ring distribution protons in the Earth's magnetosphere, and dynamics of charged particles during the excitation of magnetosonic waves. As the wave normal angle decreases, the spectral range of excited magnetosonic waves becomes broader with upper frequency limit extending beyond the lower hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 35 publications
4
48
0
Order By: Relevance
“…As the waves are strongest near Ω p 0 t = 40, electron perpendicular kinetic energy reaches the maximum, while as the waves decay later, the perpendicular energy vanishes because of weakening E × B drift. The energization characteristics found in our 2‐D simulation of the cool protons and electrons are consistent with previous 1‐D simulation in a homogeneous plasma (Sun et al, ), which offers detailed diagnosis and detailed explanation. One noteworthy point in our 2‐D simulation is that cool electron and proton energization is more efficient near the source region than outside the source region (Figures e and f), because of the greater wave intensity inside.…”
Section: Simulation Resultssupporting
confidence: 91%
“…As the waves are strongest near Ω p 0 t = 40, electron perpendicular kinetic energy reaches the maximum, while as the waves decay later, the perpendicular energy vanishes because of weakening E × B drift. The energization characteristics found in our 2‐D simulation of the cool protons and electrons are consistent with previous 1‐D simulation in a homogeneous plasma (Sun et al, ), which offers detailed diagnosis and detailed explanation. One noteworthy point in our 2‐D simulation is that cool electron and proton energization is more efficient near the source region than outside the source region (Figures e and f), because of the greater wave intensity inside.…”
Section: Simulation Resultssupporting
confidence: 91%
“…Corresponding to the wave energy, Figure shows the azimuthal component of proton kinetic energy normalized to the initial value. The azimuthal component is chosen to diagnose the perpendicular heating because the sloshing motion of background protons—a linear response to the pumping wave—occurs predominantly in the direction of spatial variation (i.e., radial direction for the present case) (e.g., Sun et al, , Figure 9). Corresponding to the wave absorption, the heating appears to occur near the seventh harmonic at tΩp,ref40 in the warmer plasma.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Since MS waves were discovered several decades ago, a large number of studies, including theoretical works and particle‐in‐cell simulations, satellite observations, and statistical surveys, have been carried out to investigate the generation of MS waves. The results demonstrate that the background plasma and source particles are the two key factors to the wave generation [ Kennel , ; Chen et al ., ; Sun et al ., , , ]. Especially, a recent study, using detailed satellite data, has revealed that MS waves can be locally excited by protons with a ring distribution in velocity space [ Balikhin et al ., ].…”
Section: Introductionmentioning
confidence: 99%